Harms – Gogol – Dostoevsky (“Old Women” – “Vij” – “Crime and Punishment”) - Shults, Sergey (Slavica, 2018)
In terms of historical poetics and intertextuality, parallels are drawn between "Old Woman"by D. Harms, "Vij" by N. Gogol and "Crime and Punishment" by F. Dostoevsky. As far as thethree authors are concerned, their common features are revealed, together with the transformationof the motives of the ugly infernal old woman, which are depicted in the context ofmythopoetics, historiosophy and social history by the three authors. Concerning the texts producedby their followers the term “post-text” is introduced, which is meant to include the dialogicalconnotations of literary evolution. The role of “vertex composition” (a term coined byV.M. Zhirmunsky) in works of Modernism/ Avant-garde is also touched upon.